2011
DOI: 10.1111/j.2044-8279.2011.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a school reform on longitudinal stability of students’ preferences with regard to education

Abstract: Stability of Preferences 2 2 AbstractBackground. Students' perspective on education is of crucial importance for its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…In a longitudinal follow-up study, a remarkable drop in students' preference for student autonomy could be observed, which could possibly be explained by a failed educational innovation in this country during the years of the study aiming at fostering students' active and self-regulated learning. The drop was larger for students with a certificate-oriented motivation and smaller for students high on self-regulation (Konings et al 2012).…”
Section: Relations Of Learning Patterns With Contextual Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a longitudinal follow-up study, a remarkable drop in students' preference for student autonomy could be observed, which could possibly be explained by a failed educational innovation in this country during the years of the study aiming at fostering students' active and self-regulated learning. The drop was larger for students with a certificate-oriented motivation and smaller for students high on self-regulation (Konings et al 2012).…”
Section: Relations Of Learning Patterns With Contextual Factorsmentioning
confidence: 99%
“…All these instruments have in common that they are self-report instruments where students are asked to indicate on a Likert-scale the extent to which the activity, view, B-or motive as described in the statement corresponds to their own way of learning, views or motives. Similarly, questionnaires have been used to study students' perceptions of their learning environment, for example the Course Experience Questionnaire (CEQ; Ramsden 1991;Law and Meyer 2011a), and the Inventory of Perceived Learning Environments Extended (IPSEE; Konings et al 2012).…”
Section: Methodological Advances In Learning Patterns Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because these students were offered increased autonomy over their learning in Studio STEM, these strong supports were likely important to maintaining their positive success beliefs while regularly engaging in meaningful decisionmaking. Research suggests that students with lower success beliefs often prefer less autonomy (Könings, Brand-Gruwel, & Elen, 2012) and perform worse when given ample freedom (Tai, Sadler, & Maltese, 2007).…”
Section: Successmentioning
confidence: 99%
“…La perspectiva de los estudiantes en su educación es de crucial importancia para desempeñarse con eficiencia, pero la opinión de los estudiantes es a menudo reconocida, tanto por los profesores, como por los directivos que diseñan sus procesos educativos, tal como lo mencionan Könings y colaboradores (13). La participación de los estudiantes en el proceso de diseño de los modelos educativos puede ser eventual y deseable para obtener un mayor compromiso de ellos con su aprendizaje.…”
Section: Discussionunclassified